Exploring the health benefits of raw white garlic consumption in humans: a mini review - Fejes, Rebeka; Bondonno, Catherine P.; Radavelli-Bagatini, Simone; Kühn, Tilman; Wagner, Karl-Heinz (Frontiers in Nutrition, 2024)
Introduction: Raw white garlic, a fundamental food in both culinary and medicinal practices globally, has gained attention for its potential health benefits. Despite widespread use, clinical research has predominantly focused on aged black garlic or garlic extracts, leaving raw white garlic consumption in humans underexplored. This mini review aims to summarize the evidence from clinical and observational studies on the health effects of raw white garlic consumption. Methods: A search in PubMed and Scopus databases was conducted to identify clinical and observational studies on raw white garlic consumption. Twelve clinical trials and ten observational studies meeting the predefined inclusion criteria were selected for review. Results: Results from clinical trials revealed diverse health effects of raw garlic consumption, including improved lipid profiles, blood pressure regulation, fibrinolytic activity, antioxidant status, and glucose metabolism. Observational studies reported the association of raw garlic consumption with improvements of important health outcomes, including cancer risk, cardiovascular disease, insulin homeostasis, and liver function. However, both clinical and observational studies were heterogenous in design, participant characteristics, durations, and outcome measures. Observational studies were limited to Asian populations. Conclusion: While human studies indicate that raw garlic may exert various health benefits, larger randomized controlled trials with longer follow-up and cohort studies are needed to explore the full potential of raw garlic consumption in human health promotion. Our mini-review aims to summarize the currently available evidence on raw garlic consumption in humans.